Computer-mediated communication in computer-assisted language learning: implications for culture-centered design - Parmaxi, Antigoni; Zaphiris, Panayiotis (My University, 2016)
This study explores the research development pertaining to computer-mediated communication (CMC) in the field of computer-assisted language learning (CALL). The basic premise of this study is that language and consequently communication are essential elements of culture; thus, deep understanding of the role of technology in facilitating communication in online environments can deepen our understanding of the notion of culture and contribute to the specification of a universal design approach in culture-centered design. The authors applied a six-stage approach for conducting a systematic review of the research development in CALL between January 2009 and September 2010. This approach resulted in the development of the CALL map which consisted of 11 themes with which CALL researchers are concerned. This study focuses on CMC, a category which maintains its popularity for more than a decade, thus sustaining itself as a major area in the field. The review brings to the forefront key themes and findings of research in these areas, as well as core concepts emerging from the literature. The study discusses empirical findings and delineates how CMC can enhance language learning, concluding with possible future directions and implications for research and practice.
Keywords: Taxonomy; Research synthesis; Research review; Inclusive design; User interface design; Culture centered; Cross-cultural; Intercultural competence